Analisis Motivasi Kehadiran Mahasiswa Fakultas Ekonomi Universitas Islam Indonesia (Pendekatan Teori Pengharapan) - Suhartini Suhartini; Romy Gustiansyah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
This Research reports the level of student’s attendance motivation at Economic Faculty of Indonesian Islamic University by using the expectancy theory model. There are three variables of expectancy theory that use to measure the attendance motivation (Y) according E. Lawler: effortsattendance (X1), attendanceoutcome (X2) and the valences of outcome (X3). This Research also reports which is the most dominant independent variables between X1, X2 and X3 that influences the dependent variable (Y) and also the influences of the different study program with attendance motivation level.The first hypothesis is: the valence of outcome is the most dominant variable that influences the attendance motivation level. The second one is: there are any different at attendance motivation level based on their study program. The results show that student’s attendance motivation at Economic Faculty of Indonesian Islamic University is high enough. The most dominant independent variable is effort  attendance and there are any different at attendance motivation level based on their study program. Specially at IESP student which have lower attendance motivation level than Management and Accountancy student.Keywords: Motivate, Expectation, effortsattendance, attendanceoutcome and the valences of outcome